Investigation of solitons in magneto-optic waveguides with Kudryashov’s law nonlinear refractive index for coupled system of generalized nonlinear Schrödinger’s equations using modified extended mapping method - Ahmed, Karim K.; Badra, Niveen M.; Ahmed, Hamdy M.; Rabie, Wafaa B.; Mirzazadeh, Mohammad; Eslami, Mostafa; Hashemi, Mir Sajjad (Nonlinear Analysis: Modelling and Control, 2024)
In this work, we investigate the optical solitons and other waves through magneto-optic waveguides with Kudryashov’s law of nonlinear refractive index in the presence of chromatic dispersion and Hamiltonian-type perturbation factors using the modified extended mapping approach. Many classifications of solutions are established like bright solitons, dark solitons, singular solitons, singular periodic wave solutions, exponential wave solutions, rational wave, solutions, Weierstrass elliptic doubly periodic solutions, and Jacobi elliptic function solutions. Some of the extracted solutions are described graphically to provide their physical understanding of the acquired solutions.
Keywords: optical solitons; magneto-optic waveguides; Kudryashov’s law; modified extended mapping technique